Intestinal Obstruction in Neonates and Children: Modern Concepts in Epidemiology, Imaging, And Surgical Care (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Intestinal obstruction remains one of the most critical emergency conditions in pediatric surgery, accounting for a significant proportion of neonatal and childhood surgical admissions. This review synthesizes current evidence on epidemiology, etiologic patterns, clinical presentation, diagnostic imaging, and contemporary management strategies. Particular emphasis is placed on major etiologic groups, including intussusception, congenital intestinal atresia and stenosis, malrotation with midgut volvulus, adhesive small bowel obstruction, Hirschsprung disease, and functional paralytic ileus. Advances in ultrasonography, non-operative enema reduction techniques, minimally invasive surgery, and neonatal intensive care have markedly improved patient outcomes. Nevertheless, delayed diagnosis continues to contribute substantially to morbidity and mortality, especially in neonates with necrotizing enterocolitis or late-presenting volvulus. Strengthening prenatal detection, early clinical recognition, and multidisciplinary management pathways is essential for further reducing complications and improving long-term outcomes in pediatric intestinal obstruction.